Trends and prospects of Nigeria's agricultural exports - Olayide, S. Olajuwon; Olatunbosun, Dupe ([Ibadan] : Nigerian Institute of Social and Economic Research, 1972)
This study attempts to take a more meaningful and quantitative look at some major commodity exports and their past and possible future influences on Nigeria's economic development
Bibliography: p. 125-[128]
osc 08/03/2019
Loans
Keywords: Produce trade; Exports; Nigeria